Laser glazing of a quasicrystal-reinforced Al-Cu-Fe-Cr alloy: Implications for use in additive manufacturing. (15th March 2023) - Yavas, Baris; Hung, Cain J.; Li, Mingxuan; Hebert, Rainer J.; Alpay, S. Pamir; Aindow, Mark
Abstract: Quasicrystal-reinforced aluminum metal matrix composites exhibit combinations of properties that are attractive for metal additive manufacturing. It is challenging to evaluate such systems due to difficulties in modeling the solidification and microstructural evolution. Here, laser glazing in a powder bed fusion instrument was used as an efficient method to evaluate an Al85 Cu6 Fe3 Cr6 alloy, and the resulting microstructures were characterized using electron microscopy. The arc-melted alloy contained only crystalline phases, but pre-glazing of the surface gave a refined microstructure comprising I-phase quasicrystals, Al2 Cu and FCC Al. Individual laser tracks produced in this layer under different conditions exhibited an extremely fine and uniform phase mixture with over 70% by volume of I-phase in a FCC Al matrix with a thin film of Al2 Cu at the interface, and no cracking or macrosegregation. The reasons for the formation of I-phase, rather than the D-phase that has been reported previously in this alloy, are discussed. Graphical abstract: Image, graphical abstract